Correction: Toward mapping pragmatic impairment of autism spectrum disorder individuals through the development of a corpus of spoken Japanese. - Sumi Kato; Kazuaki Hanawa; Vo Phuong Linh Nguyen; Manabu Saito; Ryuichi Iimura; Kentaro Inui; Kazuhiko Nakamura (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0264204.].